IPTEKS PROSEDUR PEMBERIAN KREDIT KONSUMTIF DI PT. BANK SULUTGO CABANG PEMBANTU BAHU - Supardi, Rendi Yehezkiel; Saerang, David P. E. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Indonesia’s Banking Industry are quite important for the national economy growth nowadays. As an intermediary establishment between funders and creditors, banks hold a very important role in contributing to the continuation of the nation’s wheel of economic activities. PT. Bank SulutGo specifically of the Support Branch in Bahu, is one of the financial institutions that can provide financial assistance for and from the community whilst also channel it back to the community in the process of giving a feed backs. PT. Bank SulutGo has an important role in channeling funds in the form of loans, namely cunsomer loans. The purpose of this study is to analyze those previously mentioned procedures at PT. Bank SulutGo. Based on the results obtained, PT. Bank SulutGo by now has carried out of 7 stages of procedures namely filling of file submissions, file investigations, inteviews, credit decisions, signing of credit agreements/other agreements, credit realization and fund disbursement/withdrawal. Suggerstions given for PT. Bank SulutGo Support Branch in Bahu, is to auxiliary branches and take preventive actions and carry out ongoing actions against creditors.Keywords : Bank, Credit, Consumer Credit, Credit Procedure, Non Performing Loans